2012 IEEE Congress on Evolutionary Computation 2012
DOI: 10.1109/cec.2012.6256160
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary multi-objective optimization of trace transform for invariant feature extraction

Abstract: Abstract-Trace transform is one representation of images that uses different functionals applied on the image function. When the functional is integral, it becomes identical to the well-known Radon transform, which is a useful tool in computed tomography medical imaging. The key question in Trace transform is to select the best combination of the Trace functionals to produce the optimal triple feature, which is a challenging task. In this paper, we adopt a multi-objective evolutionary algorithm adapted from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Although there was no significant increase in the identification rate compared to the classical Trace functional [17], the computational cost was reduced because only eight signatures were used instead of 22 in [17]. This paper presents a substantial extension of our preliminary work reported in [24], [25]. New contributions of the paper are as follows.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although there was no significant increase in the identification rate compared to the classical Trace functional [17], the computational cost was reduced because only eight signatures were used instead of 22 in [17]. This paper presents a substantial extension of our preliminary work reported in [24], [25]. New contributions of the paper are as follows.…”
Section: Introductionmentioning
confidence: 95%
“…Most recently, research effort has been dedicated to selecting the optimal combinations of functionals in Trace transform. In an earlier work [24], [25], we used evolutionary algorithms to find the best combinations of the classical Trace functionals, thereby reducing the computational cost while maintaining high identification performance for RST invariant image identification. Frias-Velazquez et al [26] proposed a feature selection methodology based on Laguerre polynomials by minimizing the dependency among signatures from functionals of the classical Trace transform and tested the method on vehicle identification.…”
Section: Introductionmentioning
confidence: 99%
“…In [8] a reinforcement learning algorithm was applied to the weighted Trace transform (WTT) to find the optimal threshold in the WTT space to minimize the within-class variance only. Recently, in [6], an Evolutionary Trace Transform (ETT) is developed for invariant feature extraction. It has been shown that ETT outperforms the traditional TT in extracting robust triple features from images.…”
Section: Evolutionary Trace Transformmentioning
confidence: 99%
“…The main idea is to find optimal combinations of the functionals together with the number of projections in Trace transform to achieve fast and robust feature extraction. It has been shown that evolutionary Trace transform is more robust and efficient than the traditional Trace transform [6]. This paper compares two methods of Evolutionary Trace Transform, method I and II, developed using multi-objective evolutionary optimization of Trace transform to produce candidate features of digital images.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation